(untitled) (An Nawawi, 2025)
This study aims to comprehensively analyze the implementation of Islamic economic principles in the modern financial system, encompassing the development of financial instruments, challenges and opportunities for halal SME development, the role of zakat and waqf, and the dynamics of Islamic management in Islamic financial institutions. The method used is a systematic literature review (SLR) of 47 national and international journal articles published in the last ten years. The findings reveal that the principles of prohibiting usury (riba), profit-sharing (mudharabah and musharakah), istishna’ financing instruments, as well as productive zakat and waqf, hold great potential in creating a just, inclusive, and sustainable financial system. The main challenges of implementation include weak regulation, a lack of competent human resources, low public literacy on Islamic financial products, and minimal innovation in digital-based financing models. This study emphasizes the need for institutional strengthening, regulatory harmonization, and multi-stakeholder synergy to optimize the role of the Islamic economy in national economic development.